Achieving sustainable development goals through capacity building improvement for micro and small businesses around Masjid Al Syakirin Gombak Malaysia - Yaya, Rizal; Putra, Wahyu Manuhara; Saputri, Amanda Arya; Abdiriya, Budi; Jalaludin, Dayana; Ahmad Fadzillah, Nurrulhidayah; Abdul Razak, Dzuljastri (Universitas Muhammadiyyah, Jakarta, 2024)
This study evaluates a community service program conducted for micro and small businesses around Masjid Al-Syakirin in Gombak, Malaysia. The program aims to contribute to sustainable development goals (SDGs) by enhancing capacity in three critical areas: halal product certification, risk management, and manual accounting practices. By providing targeted training and support, the program seeks to empower local entrepreneurs with the knowledge and skills necessary for business growth and sustainability. Participants reported significant gains in understanding halal certification processes, which are vital for compliance and market expansion within the Muslim community. The program also addressed risk management, equipping businesses with strategies to identify, assess, and mitigate potential risks, thereby enhancing resilience and stability. Furthermore, the training on manual accounting practices improved financial literacy and decision-making capabilities, leading to better financial management and business performance. Feedback from participants indicates a high level of satisfaction, with many acknowledging the practical benefits and immediate applicability of the knowledge gained. The training sessions not only fostered individual business growth but also encouraged a communal approach to sharing knowledge, thus multiplying the program's impact. Overall, the community service program around Masjid Al-Syakirin demonstrates a successful model for achieving the SDGs through capacity building. It highlights the importance of tailored educational initiatives for fostering sustainable economic development at the grassroots level. The findings underscore the potential for similar programs to support micro and small entrepreneurs in other regions, contributing to broader sustainable development objectives.